1995
DOI: 10.1038/ng1095-198
|View full text |Cite|
|
Sign up to set email alerts
|

The carrier frequency of the BRCA1 185delAG mutation is approximately 1 percent in Ashkenazi Jewish individuals

Abstract: Since BRCA1, the first major gene responsible for inherited breast cancer, was cloned, more than 50 unique mutations have been detected in the germline of individuals with breast and ovarian cancer. In high-risk pedigrees, female carriers of BRCA1 mutations have an 80-90% lifetime risk of breast cancer, and a 40-50% risk of ovarian cancer. However, the mutation stats of individuals unselected for breast or ovarian cancer has not been determined, and it is not known whether mutations in such individuals confer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
308
4
4

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(318 citation statements)
references
References 22 publications
2
308
4
4
Order By: Relevance
“…A common ancestor is likely to explain recurrent mutations in a defined geographical region, although this has not yet been confirmed with haplotype analysis for our population. This has clearly been shown in a number of defined ethnic and geographical populations (Struewing et al, 1995;Johannsson et al, 1996;Peelan et al, 1997;Richards et al, 1997;Thorlacius et al, 1997). Redesigning primers for SSCP/HD analysis of the regionally detected mutations allows a cheap initial mutation detection strategy and is likely to be the most appropriate approach in a regionally based diagnostic genetics laboratory.…”
Section: Discussionmentioning
confidence: 79%
“…A common ancestor is likely to explain recurrent mutations in a defined geographical region, although this has not yet been confirmed with haplotype analysis for our population. This has clearly been shown in a number of defined ethnic and geographical populations (Struewing et al, 1995;Johannsson et al, 1996;Peelan et al, 1997;Richards et al, 1997;Thorlacius et al, 1997). Redesigning primers for SSCP/HD analysis of the regionally detected mutations allows a cheap initial mutation detection strategy and is likely to be the most appropriate approach in a regionally based diagnostic genetics laboratory.…”
Section: Discussionmentioning
confidence: 79%
“…These estimates were based on studies of breast and ovarian cancer families and thus may select for women who have other mutations that further pre-dispose to cancer. Population-based studies revealed that specific germ-line mutations of BRCA1 (185delAG and 5382insC) or BRCA2 (6174delT) occurred relatively frequently in Ashkenazi Jews (up to 1% each); and their combined frequency exceeded 2% (Streuwing et al, 1995(Streuwing et al, , 1997Roa et al, 1996). This contrasts with an estimated BRCA1 mutation frequency in the general population of about 0.06% .…”
Section: Population-based Studiesmentioning
confidence: 91%
“…Inherited mutations in the human BRCA1 gene predispose individuals to early onset breast and ovarian cancer Futreal et al, 1994;Castilla et al, 1994;Friedman et al, 1994;Struewing et al, 1995;Shattuck Eidens et al, 1995;Merajver et al, 1995b). Elaboration of the disease in these individuals is frequently associated with loss of the wild type allele Cornelis et al, 1995;Merajver et al, 1995a) thus, genetically BRCA1 behaves like a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%